Spacesuit Dust Removal Techniques in Microgravity - Olson, Aaron; Mason, Julie; Bezrouk, Collin (Proceedings of the Wisconsin Space Conference, 2012)
Preventing and removing the build-up of regolith on an astronaut’s space suit is a major issue facing future manned exploration missions. The dust poses a health threat to astronauts; it also adversely affects their equipment. The Field Integrated Regolith Cleaning Experiment (FIRCE) was designed to study different techniques for removing regolith as well as reviewing what commercial off-the-shelf products were best suited for cleaning space suit orthofabric and polycarbonate (used on the astronaut’s visor). All of the commercial products worked well in both the 1-g environment as well as the 0-g environment. All were ranked above a 7.0/10 for ease of use and above 7.6/10 for cleaning effectiveness. A custom made magnetic brush, designed to attract the regolith’s static charge was not effective at removing dust because the humidity in the air prevented the build-up of static charge on the regolith.